FUNGSI PERAYAAN NEBUTA MATSURI BAGI MASYARAKAT AOMORI KEN, JEPANG - Anak Agung Ngurah Rangga Dipthaning Murti; Wayan Nurita (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2024)
A country's culture is an indispensable part of its culture, passed down from ancestors to the next generation. Similar to some other countries in the world, Japan also has a diverse culture, one of which is still running until now is the Nebuta Matsuri (ねぶた祭り) celebration in Aomori Prefecture. This research aims to find out the function of Nebuta Matsuri (ねぶた祭り) in Aomori Ken, Japan. The theory used in this research is Cultural Function Theory. The data source used is primary data collected from documentary videos related to this research used to find solutions to existing problems. The technique used to analyze the data is descriptive qualitative research technique. The results showed that in the celebration of Nebuta Matsuri (ねぶた祭り) in Aomori Ken, Japan there are three types of Nebuta Matsuri festival functions, namely: 1. Nebuta Matsuri can be used as a place to socialize, 2. Nebuta Matsuri becomes a characteristic in a community group, 3. Nebuta Matsuri as a learning medium.